2022
DOI: 10.1039/d2sc03107h
|View full text |Cite
|
Sign up to set email alerts
|

Ga and Zn increase the oxygen affinity of Cu-based catalysts for the COx hydrogenation according to ab initio atomistic thermodynamics

Abstract: In this article, we show that the surface state of Cu-based COx-hydrogenation catalysts with reducible promoters depends on the composition of the active atmosphere, and the surface becomes highly dynamic only for CO2-containing feeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 111 publications
1
16
0
Order By: Relevance
“…These results indicated that the Ni–Ga alloy nanoparticles retained their structure and composition under CO 2 hydrogenation conditions, with no evidence for dealloying/additional alloying, in agreement with the study of Hejral et al using unsupported Ni–Ga nanoparticles . The behavior observed for Ni–Ga/SiO 2 contrasts what have been observed for other bimetallic catalysts (i.e., Cu–Zn, Cu–Ga, , Pd–Ga) synthesized via the same SOMC approach used in this work, where dealloying, even if partial, was always observed under CO 2 hydrogenation conditions. ,,,, Note that the absence of bulk dealloying was also observed for the Au–Zn/SiO 2 system (Au:Zn ca. 33:67) .…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results indicated that the Ni–Ga alloy nanoparticles retained their structure and composition under CO 2 hydrogenation conditions, with no evidence for dealloying/additional alloying, in agreement with the study of Hejral et al using unsupported Ni–Ga nanoparticles . The behavior observed for Ni–Ga/SiO 2 contrasts what have been observed for other bimetallic catalysts (i.e., Cu–Zn, Cu–Ga, , Pd–Ga) synthesized via the same SOMC approach used in this work, where dealloying, even if partial, was always observed under CO 2 hydrogenation conditions. ,,,, Note that the absence of bulk dealloying was also observed for the Au–Zn/SiO 2 system (Au:Zn ca. 33:67) .…”
Section: Results and Discussionsupporting
confidence: 91%
“…25 The behavior observed for Ni−Ga/SiO 2 contrasts what have been observed for other bimetallic catalysts (i.e., Cu−Zn, 31 Cu−Ga, 10,12 Pd−Ga 18 ) synthesized via the same SOMC approach used in this work, where dealloying, even if partial, was always observed under CO 2 hydrogenation conditions. 12,18,31,59,60 Note that the absence of bulk dealloying was also observed for the Au−Zn/SiO 2 system (Au:Zn ca. 33:67).…”
Section: Catalysts' Structure During Co 2 Hydrogenation To Methanol C...mentioning
confidence: 66%
“…their chemical potentials. 3,4 This complexity poses a signicant challenge for elucidating the distribution and nature of active sites, even when using advanced in situ/operando spectroscopic techniques and state-of-the-art computational modelling. 5 For instance, state-of-the-art bimetallic NP catalysts for the selective hydrogenation of CO 2 to methanol exemplify the complexity of dynamic alloying processes as a function of chemical potential or reaction conditions (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1b). 4,21 To answer these questions, we confront experimental observations (XAS, chemisorption, CO-adsorption IR) on this well-dened SOMC-derived catalyst with simulations to explore the structural space of PdGa NPs around the free energy minimum under various reactive environments. We rst rene the structure of PdGa NPs and study the inuence of the SiO 2 support on their structure, before addressing the morphological changes of PdGa NPs under different reactive gas atmospheres-H 2 , CO, and oxidizing conditions that correspond to CO 2 hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation